Human Resource Development Strategy at Muljono Air Base in Facing Data Security Challenges in the Era of Technology 5.0 - Hardiyanto, Bagus; Yosepha, Sri Yanthy (Dinasti International Journal of Management Science, 2025)
Digital transformation in the Society 5.0 era has created new challenges in data security, particularly in the military environment. This study aims to analyze human resource (HR) development strategies at Muljono Air Base in responding to cybersecurity threats. Using a qualitative approach with a case study method, data was obtained through in-depth interviews, participant observation, and documentation studies. The results indicate that strengthening digital literacy, cybersecurity training, and collaboration with external institutions are essential pillars in building military data resilience. The main obstacles faced include budget limitations, infrastructure limitations, and personnel digital skill gaps. Therefore, HR development strategies need to be systematically designed through a technology-based training roadmap and policies that adapt to the dynamics of digital threats. The findings of this study provide practical contributions to the formulation of military HR development policies that are more responsive to technological challenges. Furthermore, the proposed strategy can serve as an implementation model for other military bases in enhancing national digital defense readiness.